SOCIO-ECONOMIC IMPACT AND PROFITABILITY ANALYSIS OF FISH FARMING IN LAGOS STATE, NIGERIA - Mebude, A. M.; Sanni, M.A.; Oyegunwa, A.S. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study evaluates the socio-economic impact and profitability analysis of fish farming in Lagos State, Nigeria. A total of 120 fish farmers were surveyed using a structured questionnaire, with data analyzed through descriptive statistics. The results reveal that 91.7% of respondents identified income generation as the primary benefit of fish farming, followed closely by employment creation (90%) and improved protein intake (87.5%). Fish farming contributes significantly to the socio-economic status of 66.7% of respondents, with a mean socio-economic score of 22.45 (SD = 7.94). However, 33.3% reported a low contribution, highlighting disparities linked to farm size and access to resources. Profitability analysis shows an average return of ₦2.27 for every ₦1 invested, with total revenue per production cycle amounting to ₦5,040,000 and a net farm income of ₦3,497,300. Feed costs constitute the largest portion of expenses, accounting for 78.41% of total variable costs. Despite the profitability, challenges such as high feed costs (Findings) and limited access to finance persist (findings), impacting the sector’s growth potential. The findings suggest that fish farming plays a crucial role in economic empowerment and food security in coastal Lagos but requires policy interventions to address key challenges.